Pulmonary endarterectomy for chronic thromboembolic pulmonary hypertension in Cape Town, South Africa - Davies-Van, Es Sophie (Department of Medicine, 2024)
Introduction: Pulmonary endarterectomy (PEA) is the only definitive and potentially curative therapy for chronic thromboembolic pulmonary hypertension (CTEPH), associated with impressive improvements in symptoms and haemodynamics. However, it is only offered at a few centres in South Africa. The characteristics and outcomes of patients undergoing PEA in Cape Town have not been previously reported. Methods and objectives: We interrogated the Adult Cardiothoracic Surgery database at the University of Cape Town (UCT) between December 2005 and April 2021 for patients undergoing PEA at Groote Schuur Hospital and Netcare UCT Private Academic Hospital. The primary outcome was the difference in World Health Organisation (WHO) functional class (WHO-FC) before and at least 6 weeks after surgery. Results: A total of 32 patients underwent PEA: 8 patients were excluded from the final analysis due to incomplete data or a histological diagnosis other than CTEPH. The workup of these patients for surgery was variable: all had CT pulmonary angiograms, 7 (29%) had ventilation: perfusion scans, 5 (21%) underwent right heart catheterisation, and none had pulmonary angiograms. The perioperative mortality was 4/24 (17%): 1 patient (4%) had a cardiac arrest on induction of anaesthesia, 2 patients (8%) died of postoperative pulmonary haemorrhage, and 1 patient (4%) died of septic complications in the intensive care unit. In survivors, the median (IQR) improvement in WHO-FC was 2 classes (1-3, p=0.0004); 10/16 patients (63%) returned to a normal baseline (WHO-FC I).